PENGARUH MOTIVASI KERJA TERHADAPKINERJA KARYAWAN OPERASIONAL DI KYRIAD BUMIMINANG HOTEL PADANG - Yetti, Silvia; Kasmita, Kasmita; Ferdian, Feri (Journal of Home Economics and Tourism, 2017)
The purpose of research is to know and revealed how motivation work andemployee performanceAnd the influence of Work Motivation on EmployeePerformance of operational departement, This research is quantitative descriptiveresearch with causal associative method. Population in this research is allemployee of operational part Kyriad Bumiminang Hotel Padang, 40 samplingtechnique technique in this research using total population technique, Datacollection techniques with a structured questionnaire based on Likert scale thathas been tested for validity and reliability. Then used normality, homogenity andlinearity and Simple linear regression and coefficient of determination test, usedSPSS 16,00. The result of this research concludes that, (1) Employee motivation isin good category (67%) (2) Employee performance is in very good category(55%), (3) result of research indicate there is positive and significant influence19% Between work motivation variable to employee performance of operationalKeywords: work motivation and employee performance of operational